The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jadohealth.2013.10.205
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Types of Harassment: Associations With Emotional Well-Being and Unhealthy Behaviors in Adolescents

Abstract: Purpose To explore relationships between harassment (i.e., race-, weight-, SES-based, sexual) and health-related outcomes, including self-esteem, depressive symptoms, body satisfaction, substance use, and self-harm behavior, among diverse adolescents. Method Cross-sectional analysis using data from a population-based study with socioeconomically and racially/ethnically diverse sample (81% racial/ethnic minority; 54% low or low-middle income) of adolescents participating in Eating and Activity in Teens 2010 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
155
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(174 citation statements)
references
References 19 publications
(34 reference statements)
13
155
1
5
Order By: Relevance
“…This is an important finding because a longitudinal study examining WB and adverse eating and weight related outcomes found WB from both family and peers predicted unhealthy weight control behaviors and higher body dissatisfaction in females and higher BMI in males (Puhl et al, 2017). Our results also indicate WB was positively correlated with BMI which is consistent with previous reports (Bucchianeri et al, 2014;Feeg et al, 2014;Friedman et al, 2005;Puhl, Peterson, & Luedicke, 2013). It is evident from these results that low-income overweight and obese adolescents are dealing with stigmatizing experiences related to weight.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is an important finding because a longitudinal study examining WB and adverse eating and weight related outcomes found WB from both family and peers predicted unhealthy weight control behaviors and higher body dissatisfaction in females and higher BMI in males (Puhl et al, 2017). Our results also indicate WB was positively correlated with BMI which is consistent with previous reports (Bucchianeri et al, 2014;Feeg et al, 2014;Friedman et al, 2005;Puhl, Peterson, & Luedicke, 2013). It is evident from these results that low-income overweight and obese adolescents are dealing with stigmatizing experiences related to weight.…”
Section: Discussionsupporting
confidence: 91%
“…Higher levels of WB are associated with unhealthy coping strategies, such as eating more food (Puhl et al, 2017;Puhl & Brownell, 2006), higher body mass index (BMI; Myers & Rosen, 1999;Mamun, O'Callaghan, Williams, & Najman, 2013;Neumark-Sztainer et al, 2007;Takizawa, Danese, Maughan, & Arseneault, 2015), body dissatisfaction, and lower psychosocial functioning (Annis, Cash, & Hrabosky, 2004;Bucchianeri, Eisenberg, Wall, Piran, & Neumark-Sztainer, 2014). Additionally, obese individuals experiencing WB are at increased risk for depression and other mental health disorders (Bucchianeri et al, 2014;Friedman et al, 2005).…”
mentioning
confidence: 99%
“…A number of hypotheses can be reflected upon regarding the relationship between bullying and health compromising behaviors among adolescents. The link between bullying and problematic alcohol use has been documented among various adolescent populations [55,56]. While most of these studies have been cross-sectional, the most commonly cited hypothesis regarding this association is that it is likely a coping mechanism among those who experience the stress, shame and humiliation of being bullied [57].…”
Section: Discussionmentioning
confidence: 99%
“…Harassment of any type, particularly sexual harassment, has been linked to a variety of poor mental health and well-being outcomes, including self-harm, among adolescents. The risk of non-suicidal self-injury/self-harm, suicide attempts and completed suicide increases with the number of harassment types that an adolescent experiences 159. Early detection and intervention, which reduces the incidence of harassment, is particularly important in mitigating mental health difficulties and behavioural self-harm among adolescents 160.…”
Section: Impacts Of Non-accidental Violencementioning
confidence: 99%